Changes in women's empowerment in the household, women's diet diversity, and their relationship against the background of COVID-19 in southern Bangladesh - Lecoutere, Els; Berg, Marrit van den; de Brauw, Alan (Elsevier, 2023)
The COVID-19 pandemic in Bangladesh, associated public health measures, and people’s reactions were projected to have caused job losses among women, a decline in women’s empowerment and reduced women’s diet diversity. Using a November 2020 telephone survey to re-interview adult female respondents of a November 2019 in-person survey, contrary to expectations we find that more women found than lost jobs, and women’s diet diversity increased over the year partly marked by the COVID-19 pandemic. We did not find evidence of a decline in women’s involvement in food purchase decisions, nor women’s autonomy over use of household income. The change in women’s outside employment is neither statistically related to changes in women’s involvement in food purchase decisions, changes women’s autonomy over use of household income, nor changes in women’s diet diversity. Change in women’s involvement in food purchase decisions is positively related with change in women’s diet diversity and change in women’s autonomy over income use is negatively related with change in women’s diet diversity.